2013
DOI: 10.1371/journal.pone.0075074
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Acceptability of Male Circumcision among Men in Jamaica

Abstract: ObjectivesTo determine the prevalence of male circumcision (MC) among men in the western region of Jamaica, and to identify factors associated with acceptability of MC for self, infants (<1 year) and older sons (1-17 years).MethodsA cross-sectional, interviewer-administered questionnaire survey of 549 men aged 19-54 years was conducted in the western region of Jamaica. The survey included questions about the acceptance of MC for self, infants, and sons before and after an information session about the benefits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
2
9
1
Order By: Relevance
“…Most significantly, just over half of them were aware of the fact that VMMC can decrease the risk of HIV infection. This is consistent with studies conducted in Jamaica and Uganda, which indicated a higher proportion of awareness of male circumcision (Wilcken et al, 2010;Walcott et al, 2013). Some differences were noted on the level of awareness about the VMMC's protective effect on HIV amongst the respondents where we found that in our study it was higher as compared to other studies conducted in other regions such as East/Central Africa e.g.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Most significantly, just over half of them were aware of the fact that VMMC can decrease the risk of HIV infection. This is consistent with studies conducted in Jamaica and Uganda, which indicated a higher proportion of awareness of male circumcision (Wilcken et al, 2010;Walcott et al, 2013). Some differences were noted on the level of awareness about the VMMC's protective effect on HIV amongst the respondents where we found that in our study it was higher as compared to other studies conducted in other regions such as East/Central Africa e.g.…”
Section: Discussionsupporting
confidence: 91%
“…This will be crucial in promoting the acceptance of VMMC. It was by no surprise that even in studies conducted in Jamaica, Malawi and Uganda participants believed that male circumcision enhances sexual satisfaction (Walcott et al, 2013;Ngalande et al, 2006;Wilken et al, 2010). The acceptability of safe male circumcision among the uncircumcised respondents in our study was found to be 43.8% which was much lower than the median acceptability rate in the sub-Saharan African countries which was 65% (Westercamp and Bailey, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Details about the study setting have been described elsewhere. 32 Briefly, the WRHA consists of four parishes (St. James, Trelawny, Hanover and Westmoreland) with an estimated population of~474 944. Of the 14 parishes in Jamaica, the HIV prevalence of the parishes in the WRHA are among the highest.…”
Section: Study Design and Settingsmentioning
confidence: 99%
“…Similarly, hygiene, the most cited primary reason for having a VMMC in this study, was significantly associated with the willingness to be circumcised in our prior surveys [ 9 , 11 ]. Other studies have shown high acceptability of the procedure in Caribbean [ 12 ], Chinese [ 13 ], and Indian men [ 14 ], but to our knowledge, this is the first attempt to offer VMMC services outside of Africa. Although our previous acceptability study found that Haitian men would be more willing than Dominicans to become circumcised, we did not recruit a significant number of Haitian nationals.…”
Section: Discussionmentioning
confidence: 96%